Iron and manganese deposits of the Urucum District, Mato Grosso do Sul, Brazil - Urban, Hans; Stribrny, Bernhard; Lippolt, Hans J. (Economic geology, 1992)
The Urucum district is located in the Brazilian state of Mato Grosso do Sul near the city of Corumba on the Brazilian-Bolivian border. The district comprises an area of 200 km 2 , where eight up to 1,000-m-high tabular mountains rise out of the swampy lowlands of the Pantanal. The tabular mountains are partly built by an up to 350-m-thick rock sequence of the Santa Cruz Formation. From bottom to top, the Santa Cruz Formation is composed of manganese ore horizon Mn 1, an 80-m-thick unit of ferruginous sandstones, and manganese ore horizon Mn 2, which is overlain by an up to 270-m-thick monotonous sequence of hematite-jaspilites. Forty meters above Mn 2 is manganese ore horizon Mn 3; another 40 m above Mn 3 is manganese ore horizon Mn 4. Both are intercalated with the hematite-jaspilites. The iron ore reserves of the Urucum district amount to approximately 36 billion tons. The calculation of the manganese ore reserves in the four horizons results in 608 million tons, comprised of 23.4 million tons of measured, 34.5 million tons of indicated, 465.1 million tons of inferred, and 86 million tons of hypothetical and speculative reserves. In the Urucum district predominantly layered, detritus-rich, and concretionary cryptomelane ores are found. The ores consist mainly of micro- to cryptocrystalline cryptomelane associated with hematite and quartz. Braunite, pyrolusite, and lithiophorite are minor constituents. Layered braunite ores mined are composed of braunite, cryptomelane, pyrolusite, hematite, and quartz. The average Mn contents of these four different types of manganese ores range from 25.63 percent in the detritus-rich cryptomelane ores to 49.51 percent in the concretionary ones. The fresh hematite-jaspilitic iron ores contain about 50 percent Fe, whereas in the weathered and quartz-depleted hematite-jaspilites the iron content increases to 67 percent.Most of the iron and manganese ores were precipitated as chemical sediments in a partly ice-covered, fjordlike basin. Field observations, Rb/Sr isotope studies, and leaching experiments show that large-scale solution, transport, and reprecipitation processes led to supergene concentrations of iron and manganese in the underlying sandstones at the bottom of the Santa Cruz Formation and in manganese ore horizon Mn 1.
Elektronische Reproduktion der Druck-Ausgabe 2. März 2017
Gesehen am 23.03.2023